2003
DOI: 10.1038/sj.pcan.4500652
|View full text |Cite
|
Sign up to set email alerts
|

Treatment modalities of bladder/prostate rhabdomyosarcoma: a review

Abstract: Treatment outcomes of bladder/prostate rhabdomyosarcoma (RMS) in multi-and single-institutional trials are reviewed. Remarkable strides have occurred in the treatment of this disease. Decreasing duration of chemotherapy, less cumulative doses of radiation therapy, and improving survival have been documented. A focus on bladder preservation has not adversely affected survival in most studies. Even if organ preservation is not possible, improvements in urinary diversion surgical technique still offer improved qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 69 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…This is also attributed in part to early diagnosis and timely referral to specialised centres [24]. Also, a focus on bladder preservation has not adversely affected survival in most studies [3] and in cases where organ preservation is not possible, improvements in urinary diversion techniques still offer improved quality of life [1]. Although limited reports exist in the literature about the less invasive local excision, there is mounting evidence that combination of local excision with adjuvant chemotherapy give excellent outcomes with 2-year survival rates of >96% [4,6,28].…”
Section: Discussionmentioning
confidence: 97%
“…This is also attributed in part to early diagnosis and timely referral to specialised centres [24]. Also, a focus on bladder preservation has not adversely affected survival in most studies [3] and in cases where organ preservation is not possible, improvements in urinary diversion techniques still offer improved quality of life [1]. Although limited reports exist in the literature about the less invasive local excision, there is mounting evidence that combination of local excision with adjuvant chemotherapy give excellent outcomes with 2-year survival rates of >96% [4,6,28].…”
Section: Discussionmentioning
confidence: 97%
“… 4 Ashlock et al reported improved survival and quality of life outcomes in children treated with multimodality therapy. 5 However, in adults the prognosis remains poor. The 70 Gy dose delivered to our patient allowed local control of the disease without toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Data on bladder RMS can only be extracted from studies on large series of RMS arising in different sites. Most of the available literature on bladder RMS shows its association with embryonal variants [ 16 - 18 ]. Within 65 specimens of bladder and vagina RMS, Leuschner et al found 51 urinary bladder RMS and 14 vaginal RMS.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…Despite improvements in morphological and cytological examination, as many as one third of the patients could be incorrectly assigned to treatment protocols because of inconsistency and uncertainty as determined by institutional pathology diagnosis [ 18 ]. Genomic analysis of human tumor specimens has an increasingly significant impact on the field of tumor pathology [ 23 , 24 ], redefining tumor classes based on molecular features [ 25 , 26 ] and identifying new subclasses previously unrecognized by conventional histology or cytogenetics.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%